Successful Simultaneous Liver-Kidney Transplantation in the Presence of Multiple High-Titered Class I and II Antidonor HLA Antibodies. Issue 12 (December 2016) - Paterno, Flavio; Girnita, Alin; Brailey, Paul; Witte, David; Wang, Jiang; Cuffy, Madison C.; Diwan, Tayyab; Tremblay, Simon; Revollo, Jane Y.; Alloway, Rita R.; Schoech, Michael R.; Anwar, Nadim; et al.
Abstract : Abstract: The results of simultaneous liver-kidney transplants in highly sensitized recipients have been controversial in terms of antibody-mediated rejection and kidney allograft outcomes. This case report provides a detailed and sophisticated documentation of histocompatibility and pathologic data in a simultaneous liver-kidney transplant performed in a recipient with multiple high-titered class I and II antidonor HLA antibodies and a strongly positive cytotoxic crossmatch. Patient received induction with steroids, rituximab, and eculizumab without lymphocyte depleting agents. The kidney transplant was delayed by 6 hours after the liver transplant to allow more time to the liver allograft to "absorb" donor-specific antibodies (DSA). Interestingly, the liver allograft did not prevent immediate antibody-mediated injury to the kidney allograft in this highly sensitized recipient. Anti-HLA single antigen bead analysis of liver and kidney allograft biopsy eluates revealed deposition of both class I and II DSA in both liver and kidney transplants during the first 2 weeks after transplant. Afterward, both liver and kidney allograft functions improved and remained normal after a year with progressive reduction in serum DSA values.